Genome structure reveals the diversity of mating mechanisms in Saccharomyces cerevisiae x Saccharomyces kudriavzevii hybrids, and the genomic instability that promotes phenotypic diversity. Issue 3 (17th February 2020) - Morard, Miguel; Benavent-Gil, Yaiza; Ortiz-Tovar, Guadalupe; Pérez-Través, Laura; Querol, Amparo; Toft, Christina; Barrio, Eladio
Abstract : Interspecific hybridization has played an important role in the evolution of eukaryotic organisms by favouring genetic interchange between divergent lineages to generate new phenotypic diversity involved in the adaptation to new environments. This way, hybridization between Saccharomyces species, involving the fusion between their metabolic capabilities, is a recurrent adaptive strategy in industrial environments. In the present study, whole-genome sequences of natural hybrids between Saccharomyces cerevisiae and Saccharomyces kudriavzevii were obtained to unveil the mechanisms involved in the origin and evolution of hybrids, as well as the ecological and geographic contexts in which spontaneous hybridization and hybrid persistence take place. Although Saccharomyces species can mate using different mechanisms, we concluded that rare-mating is the most commonly used, but other mechanisms were also observed in specific hybrids. The preponderance of rare-mating was confirmed by performing artificial hybridization experiments. The mechanism used to mate determines the genomic structure of the hybrid and its final evolutionary outcome. The evolution and adaptability of the hybrids are triggered by genomic instability, resulting in a wide diversity of genomic rearrangements. Some of these rearrangements could be adaptive under the stressful conditions of the industrial environment.